Health-Related Quality of Life Among Patients Who Have Survived an Episode of Sepsis in the United States: A Systematic Review - Sanjukta Basu; Ziyan J. Wei; Atara Laor; Liga Bennetts; Nina Ahmad; Antoine C. El Khoury; Jeroen Geurtsen; Maureen P. Neary (Infectious Diseases and Therapy)
Abstract Introduction Sepsis is a serious condition that may lead to death or profoundly affect the well-being of those who survive. The aim of this systematic review was to identify and summarize evidence on the impact of all-cause sepsis on health-related quality of life (HRQoL), physical, cognitive, and psychological outcomes among sepsis survivors in the USA. Methods Studies assessing HRQoL, physical, cognitive, and psychological outcomes in patients who survived an episode of sepsis and published from January 1, 2010, to September 30, 2023, were systematically identified through EMBASE, MEDLINE, and MEDLINE In-Process databases, as well as through gray literature. Results Of 2885 records identified, 7 studies (7 publications; N = 180,592 participants) met the eligibility criteria for inclusion in this review. Studies examined the effects of sepsis on the following outcomes of interest: HRQoL (4 studies), physical functioning (5 studies), cognitive status (3 studies), and psychological well-being (3 studies). After 12 months, sepsis survivors who developed chronic critical illness (N = 63) had significantly poorer HRQoL as measured by EuroQoL 5-dimensional (EQ-5D) questionnaire mean utility index score and Short Form 36-item (SF-36) physical and mental summary scores compared with patients who rapidly recovered (N = 110). Among patients admitted to a skilled nursing facility post-sepsis (N = 66,540), 34% and 72.5% had severe or very severe cognitive impairment and dependence to perform activities of daily living, respectively. Significant increase in moderate-to-severe cognitive impairment among severe sepsis survivors (N = 623) before and after sepsis was reported (median 0.9 [IQR: 0.4, 1.4] years; 6.1% and 16.7%, respectively [P < 0.001]). Substantial depression and anxiety symptoms were frequently observed post-sepsis, but with limited evidence for increased burden as assessed by specific psychological measures. Conclusion These findings underscore the profound negative impacts of sepsis on patients’ HRQoL, ability to perform activities of daily living, and cognitive abilities.